Novel insights into IL-37: an anti-inflammatory cytokine with emerging roles in anti-cancer process - Gu, Min; Jin, Yuexinzi; Gao, Xun; Xia, Wenying; Xu, Ting; Pan, Shiyang (Frontiers in Immunology, 2023)
Interleukin-37 (IL-37) is a newly discovered member of IL-1 family. The cytokine was proved to have extensive protective effects in infectious diseases, allergic diseases, metabolic diseases, autoimmune diseases and tumors since its discovery. IL-37 was mainly produced by immune and some non-immune cells in response to inflammatory stimulus. The IL-37 precursors can convert into the mature forms after caspase-1 cleavage and activation intracellularly, and then bind to Smad-3 and transfer to the nucleus to inhibit the production and functions of proinflammatory cytokines; extracellularly, IL-37 binds to cell surface receptors to form IL-37/IL-18Rα/IL-1R8 complex to exert immunosuppressive function via inhibiting/activating multiple signal pathways. In addition, IL-37 can attenuate the pro-inflammatory effect of IL-18 through directly or forming an IL-37/IL-18BP/IL-18Rβ complex. Therefore, IL-37 has the ability to suppress innate and acquired immunity of the host, and effectively control inflammatory stimulation, which was considered as a new hallmark of cancer. Specifically, it is concluded that IL-37 can inhibit the growth and migration of tumor cells, prohibit angiogenesis and mediate the immunoregulation in tumor microenvironment, so as to exert effective anti-tumor effects. Importantly, latest studies also showed that IL-37 may be a novel therapeutic target for cancer monitoring. In this review, we summarize the immunoregulation roles and mechanisms of IL-37 in anti-tumor process, and discuss its progress so far and potential as tumor immunotherapy.